Influence of play on positive psychological development in emerging adulthood: A serial mediation model - Ho, Wing W. Y. (Frontiers in Psychology, 2022)
Although the literature reports that play provides substantial psychological benefits for individuals, it is often only emphasized by educators for younger children but less so for emerging adults. This cross-sectional study examined the impact of time spent engaged in play on emerging adults' emotional intelligence, emotional traits, and resilience. Participants (N = 131, 93.9% women) were full-time undergraduate students between the ages of 19 and 25 (M = 21.28, SD = 1.08). Results showed that play experiences cultivated emotional intelligence and strengthened resilience. Further, the findings supported a serial mediation model in which play was indirectly related to resilience through its effect on emotional intelligence and positive emotion. Play is recognized as a means to relieve stress and protect psychological well-being. Emerging adults who experience pleasure, enjoyment, learning, and the acquisition of new skills will benefit from play. Individuals should enhance positive play experiences, particularly sporting activities, to maintain a healthy work-life balance given the positive relationship between play, emotional intelligence, emotional traits, and resilience.